Altered cytoskeletal arrangement in induced pluripotent stem cells and motor neurons from patients with riboflavin transporter deficiency - Alessia Niceforo; Chiara Marioli; Fiorella Colasuonno; Stefania Petrini; Keith Massey; Marco Tartaglia; Enrico Bertini; Sandra Moreno; Claudia Compagnucci (The Company of Biologists, 2021)
The cytoskeletal network plays a crucial role in the differentiation, morphogenesis, function and homeostasis of the nervous tissue, so that alterations in any of its components may lead to neurodegenerative diseases. Riboflavin transporter deficiency (RTD), a childhood-onset disorder characterized by degeneration of motor neurons (MNs), is caused by biallelic mutations in genes encoding the human riboflavin (RF) transporters. In a patient-specific induced pluripotent stem cells (iPSCs) model of RTD, we recently demonstrated altered cell-cell contacts, energy dysmetabolism and redox imbalance. The present study focuses on cytoskeletal composition and dynamics associated to RTD, utilizing patients' iPSCs and derived MNs. Abnormal expression and distribution of α- and β-tubulin (α- and β-TUB), as well as imbalanced tyrosination of α-TUB, accompanied by an impaired ability to re-polymerize after nocodazole treatment, were found in RTD patient-derived iPSCs. Following differentiation, MNs showed consistent changes in TUB content, which was associated with abnormal morphofunctional features, such as neurite length and Ca2+ homeostasis, suggesting impaired differentiation. Beneficial effects of RF supplementation, alone or in combination with the antioxidant molecule N-acetyl cystine (NAC), were assessed. RF administration resulted in partially improved cytoskeletal features in patients' iPSCs and MNs, suggesting that redundancy of transporters may rescue cell functionality in the presence of adequate concentrations of the vitamin. Moreover, supplementation with NAC was demonstrated to be effective in restoring all the considered parameters, when used in combination with RF, thus supporting the therapeutic use of both compounds.